Imaging NRF2 activation in non-small cell lung cancer with positron emission tomography - Hannah E. Greenwood; Abigail R. Barber; Richard S. Edwards; Will E. Tyrrell; Madeleine E. George; Sofia N. dos Santos; Friedrich Baark; Muhammet Tanc; Eman Khalil; Aimee Falzone; Nathan P. Ward; Janine M. DeBlasi; et al. (Nature Communications)
Abstract Mutations in the NRF2-KEAP1 pathway are common in non-small cell lung cancer (NSCLC) and confer broad-spectrum therapeutic resistance, leading to poor outcomes. Currently, there is no means to non-invasively identify NRF2 activation in living subjects. Here, we show that positron emission tomography imaging with the system xc − radiotracer, [18F]FSPG, provides a sensitive and specific marker of NRF2 activation in orthotopic, patient-derived, and genetically engineered mouse models of NSCLC. We found a NRF2-related gene expression signature in a large cohort of NSCLC patients, suggesting an opportunity to preselect patients prior to [18F]FSPG imaging. Furthermore, we reveal that system xc − is a metabolic vulnerability that can be therapeutically targeted with an antibody-drug conjugate for sustained tumour growth suppression. Overall, our results establish [18F]FSPG as a predictive marker of therapy resistance in NSCLC and provide the basis for the clinical evaluation of both imaging and therapeutic agents that target this important antioxidant pathway.